The Concept of Talent Management as a Special Category of Organization Employees - T. N. Kurina (Управленческие науки)
The article is devoted to a special category of employees who have a unique set of qualities necessary to achieve the strategic goals of the organization. The importance of such employees for the development of companies, as well as the need to find innovative approaches to talent management. Special attention is paid to high-potential employees. The author considers the practical experience of the talent management system implementation in a large Russian company. The proposed system allows the company not only to achieve results in key areas, but also to maintain its position in a highly competitive market. As a result of the study, it can be concluded that a special category of employees are the driving force of positive changes in the organization. The concept of talent management proposed in the article is aimed at the formation of a systematic approach to talent management, and it should organically fit into the overall system of personnel management.